Strengthened Synergistic Effect of Metallic MxPy (M = Co, Ni, and Cu) and Carbon Layer via Peapod‐Like Architecture for Both Hydrogen and Oxygen Evolution Reactions. Issue 16 (6th February 2017) - Bai, Yuanjuan; Fang, Ling; Xu, Haitao; Gu, Xiao; Zhang, Huijuan; Wang, Yu
Abstract : The smooth electric transmission is crucial for the high‐efficient electrocatalysis. Herein, a series of peapod‐like metallic M x P y /C (M = Co, Ni, and Cu) composites is developed as bifunctional catalysts toward hydrogen and oxygen evolution reactions. For the first time, the metallic property of Cu3 P is confirmed through the theoretical calculation. The in‐depth composition, structural and catalytic mechanism analysis of M x P y /C discloses that the comparable activity and considerable durability of these catalysts mainly result from the strengthened synergistic effect between metallic M x P y and carbon layer based on the unique peapod‐like architecture. Especially, the atomic contact between M x P y and carbon not only provides an open channel for electronic transmission but also ensures the integrity of peapod‐like structure. Furthermore, the high electric conductivity of the inner metallic M x P y and the outer carbon layer endows the M x P y /C catalyst with rapid charge migration during the electrocatalytic pathway. These findings shed light on the origin of high catalytic activity of M x P y /C and open a path for purposefully rationally synthesizing superior electrocatalysts. Abstract : Three kinds of metallic H‐CoP/C, Ni2 P/C, and Cu3 P/C nanocomposites are synthesized, which exhibit remarkable catalytic activity and stability for both the hydrogen and oxygen evolution reactions. The superior catalytic performance of these metallic M x P y /C materials is mainly contributed to the strengthened synergistic effect between metallic M x P y and carbon layer based on the unique peapod‐like architecture.